Ethnic Disparities in Imaging Utilization at Diagnosis of Non-Small Cell Lung Cancer. (5th March 2020) - Morgan, Rustain L; Karam, Sana D; Bradley, Cathy J
Abstract: Background: Prior research demonstrated statistically significant racial disparities related to lung cancer treatment and outcomes. We examined differences in initial imaging and survival between blacks, Hispanics, and non-Hispanic whites. Methods: The linked Surveillance, Epidemiology, and End Results-Medicare database between 2007 and 2015 was used to compare initial imaging modality for patients with lung cancer. Participants included 28 881 non-Hispanic whites, 3123 black, and 1907 Hispanics, patients age 66 years and older who were enrolled in Medicare fee-for-service and diagnosed with lung cancer. The primary outcome was comparison of positron emission tomography (PET) imaging with computerized tomography (CT) imaging use between groups. A secondary outcome was 12-month cancer-specific survival. Information on stage, treatment, and treatment facility was included in the analysis. Chi-square test and logistic regression were used to evaluate factors associated with imaging use. Kaplan-Meier method and Cox proportional hazards regression were used to calculate adjusted hazard ratios and survival. All statistical tests were two-sided. Results: After adjusting for demographic, community, and facility characteristics, blacks were less likely to undergo PET or CT imaging at diagnosis compared with non-Hispanic whites odds ratio (OR) = 0.54 (95% confidence interval [CI] = 0.50 to 0.59; P  < .001). Hispanics were also less likely to receive PET with CT imaging (OR = 0.72, 95% CI = 0.65 to 0.81;  P  < .001). PET with CT was associated with improved survival (HR = 0.61, 95% CI = 0.57 to 0.65; P  < .001). Conclusions: Blacks and Hispanics are less likely to undergo guideline-recommended PET with CT imaging at diagnosis of lung cancer, which may partially explain differences in survival. Awareness of this issue will allow for future interventions aimed at reducing this disparity.